Pengaruh Pelatihan Responding Empathically untuk Meningkatkan Kemampuan Respon Empatik pada Dokter di Medicuss Group Kota Bandung - Silvia Sipayung; Robert Oloan Rajagukguk; Lie Fun Fun (Humanitas (Jurnal Psikologi), 2018)
The aim of this research is to see the effect of responding emphatically training to improve doctor's skill in emphatic response in Medicuss Group Bandung. The measuring tool that being used is the scenario questionnaire based on the theory of emphatic response (Hammand, 1997) as the dependent variable tool which consists 8 items. The validity of empathic response is examined using expert validity. The research data will be analysed using quantitative method. The resuly of this research shows there are some differences in emphatic response score of doctor in Medicuss Group Bandung before and after being given the responding empathically training. The theoritical suggestion for further research is conducted a similar study using the one group pre-post test design with time series method. Suggestions for the doctor in Medicuss Group are doctor can apply the lesson during responding empathically training which is useful to support in performing the role as doctor. Keywords: Responding Empathically, Empathic Response, Doctor, Medicuss Group